(untitled) (Perner’s Contacts, 2017)
The aim of this paper is to point to shortcomings arising from the current method of security checks at international airports. There are included definitions related to security checks, their development and current situation. There are also discussed disadvantages of the current approach and submitted a proposal to modernization of security checkpoints, with an emphasis on improving the reliability of screeners and screening itself through behavioural analysis of passengers. These planned optimization measures should bring a higher level of assurance of the security restricted area of the airport and hypothetically also other strategic objects of critical infrastructure.